2008
DOI: 10.1111/j.1574-6968.2007.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

The pap1+ gene of fission yeast is transcriptionally regulated by nitrosative and nutritional stress

Abstract: In the current work, regulation of the pap1(+) gene was investigated by the use of the pap1(+)-lacZ fusion gene and semi-quantitative reverse transcriptase-PCR. The synthesis of beta-galactosidase from the pap1(+)-lacZ fusion gene was significantly enhanced by nitric oxide (NO)-generating sodium nitroprusside (SNP) and nitrogen starvation. However, the induction by SNP and nitrogen starvation was observed to be much less in the Pap1p-negative cells harboring the fusion gene. Exogenous NO was more effectively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Kong et al [7] reported that fungal cells produce endogenous NO that plays an important biological role in fungal growth or morphogenesis [4]. NO is directly involved in the regulation of gene transcription [8][9][10][11], cellular oxidative stress, thiobarbituric acid reactive substance (TBARS) production, protein Snitrosylation modification, tyrosine nitration, and trehalose accumulation [7,10,12]. These biological mechanisms are essential for maintaining fungal cell physiological activities.…”
Section: Introductionmentioning
confidence: 98%
“…Kong et al [7] reported that fungal cells produce endogenous NO that plays an important biological role in fungal growth or morphogenesis [4]. NO is directly involved in the regulation of gene transcription [8][9][10][11], cellular oxidative stress, thiobarbituric acid reactive substance (TBARS) production, protein Snitrosylation modification, tyrosine nitration, and trehalose accumulation [7,10,12]. These biological mechanisms are essential for maintaining fungal cell physiological activities.…”
Section: Introductionmentioning
confidence: 98%
“…Instead, Sarver and DeRisi have shown that the C 2 H 2 zinc finger transcription factor ScFZF1 is involved in NO sensing in S. cerevisiae [46]. In S. pombe, the AP-1-like bZIP transcription factor, SpPap1, regulates nitrosative as well as oxidative and nutritional stress responses [51]. The orthologue of SpPap1, ScYap1, regulates the oxidative stress response in S. cerevisiae .…”
Section: Nitrosative Stress Responses In the Model Yeastsmentioning
confidence: 99%